PENGENDALIAN "TOXIC PRODUCTIVITY" DALAM MENJAGA KESEHATAN MENTAL PADA MAHASISWA UNIVERSITAS NEGERI JAKARTA DI MASA PANDEMI COVID-19 - Camilla Ramadhina; Dini Safitri; Fahriza Annisa; Qynantha Fadilah (Interaksi: Jurnal Ilmu Komunikasi, 2023)
This journal was created with the aim that students can avoid an unhealthy productivity. Especially when knowing the bad impact on the mental health of each individual. Restrictions on social life that are being lived bring about certain responses that affect the comfort of human life, such as the emergence of fear and worry, feeling lonely, "distant" from the environment, to the emergence of feelings of anxiety that interfere and cause stress. The research used is qualitative where the researcher uses the interview technique process with 4 student informants from the State University of Jakarta who have core management positions in an organization. One of the things we can take is to persevere for the task which is something positive, but not to forget the real basic human needs. The solution to avoid a toxic productivity is to determine your achievements and know your limits. So that in doing something, each individual does not force himself to do an activity.